Knowledge and Attitude Regarding HIV/AIDS among Army Personnel at Army Hospital - Darai, B (Medical Journal of Shree Birendra Hospital, 2005)
Knowledge and Attitude Regarding HIV/AIDS among Army Personnel at Army Hospital